Caracterização das competências dos jogadores de futebol relativo aos diferentes estatutos posicionais - Cauan Felipe de Almeida (2016)
This dissertation intended to identify a set of indicators that allow recognizing the soccer players' skills concerning the different positional statutes. For this, first, it was tried to understand which aspects determine the player's responsible behavior in the context of the game. Based on this concern, by reviewing the specific literature of the area, it sought to relate three thematic: the football game contextualization; the characterization of the football teams organization; and, decisional context in the game and its development. That way, it was understood that the soccer player's competence, in the context of the game is related to their ability to perform specific functions effectively. Later, in order to realize which skills the soccer players should show so that they can present competence in different functions to perform. It was held a study in order to develop and validate different indicators of competence related to distinct positional statutes. For this purpose four stages were fulfilled: (i) category and subcategory definition by crossing information resulting from the specific literature; (ii) development indicators from the professional players' behavior performing the observation of qualified soccer players in different positional statutes; (iii) elaboration of a questionnaire, semi structured methodology; and (iv) expertise, sixteeen soccer experts were interviewed and they had to answer about their level of agreement (Likert adapted scale) for the different proposed indicators. For data analysis it was used the SPSS software. To describe the experts' degree of concordance for each proposed indicator it was analyzed whether the absolute and relative frequencies of the answers. The indicators validation was instituted considering the experts consensus according to a cutoff value of 80% for the results. After having achieved the expertise were validated a total of ( n=114) competence indicators related to the different positional statutes. therefore it is suggested that the indicators identification can help coaches and soccer professionals in three different dimensions: contextualize the players relatively the indicators and develop them in a longitudinal perspective through the specific practice context; put into practice possible positional statute changes according to the comparison of defined competencies for such statute; and assist in high level players selection process.